Debates and Impressions of Change and Continuity in Indonesia’s Musical Arts since the Fall of Suharto, 1998-2002 - Margaret J. Kartomi (Wacana Seni Journal of Arts Discourse, 2002)
This article discusses changes and continuities in lndonesia's musical scene since the resignation of President Suharto and his New Order regime in May 1998 following the Asian economic collapse and monetary crisis (krismon) in 1997. These events led to the beginning of the reformasi (reformation) period in 1998, which was instituted under the quick succession of Presidents B.J. Habibie (from May 1998 to October 1999), Abdurrahman Wahid (from October 1999 to November 2000) and Megawati Soekarnopoetri (from November 2000 to the time of writing). The fall of Suharto did not bring an opposition group to power; nor was there an expectation that Habibie would discontinue the policy of giving priority funding to "music for the elite" or halt the centralisation of the arts in Java, especially Jakarta, at the expense of the other regions. However, changes did occur under his rule, and those of the other two Presidents, which have had an affect on the production, distribution and consumption of the musical arts.